The Main Features of Pedagogical Activity in Educating Intellectually Talented Youth - Khaydarov Abdug'appar Toshpulatovich; Akmalova Aziza Najmiddinovna (Scientific Trends, 2025)
This article presents a brief description of the intellectual potential of young people, the characteristics of pedagogical activities in educating young people with intellectual potential,and the development of students professional potential.
Keywords: Youth intelligence, intelligence, technology, creativity, youth potential, pedagogical activity.